Prevalence and factors associated with mild depressive and anxiety symptoms in older adults living with HIV from the Kenyan coast. (29th September 2022) - Mwangala, Patrick N.; Nasambu, Carophine; Wagner, Ryan G.; Newton, Charles R.; Abubakar, Amina
Abstract: Introduction: Empirical research on the burden and determinants of common mental disorders (CMDs), especially depression and anxiety, among older adults living with HIV (OALWH) in sub‐Saharan Africa is inadequate. To bridge the gap in Kenya we: (1) determined the prevalence of CMDs among OALWH on routine HIV care compared to HIV‐negative peers; (2) investigated HIV status as an independent predictor of CMDs in older adults; and (3) investigated CMD determinants. Methods: In a cross‐sectional study conducted between 2020 and 2021, the prevalence of CMDs and associated determinants were investigated at the Kenyan coast among 440 adults aged ≥50 years (257 OALWH). The Patient Health Questionnaire and Generalized Anxiety Disorder scale were administered alongside measures capturing biopsychosocial information. Logistic regression was used to examine the correlates of CMDs. Results: No significant differences were found in the prevalence of mild depressive symptoms, 23.8% versus 18.2% ( p = 0.16) and mild anxiety symptoms, 11.7% versus 7.2% ( p = 0.12) among OALWH compared to HIV‐negative peers, respectively. HIV status was not independently predictive of CMDs. Among OALWH, higher perceived HIV‐related stigma, ageism, increasing household HIV burden, loneliness, increasing functional disability, sleeping difficulties, chronic fatigue and advanced age (>70 years) were associated with elevated CMDs. Among HIV‐negative older adults, loneliness, increased medication burden and sleeping difficulties were associated with elevated depressive symptoms. Easier access to HIV care was the only factor associated with lower CMDs among OALWH. Conclusions: On the Kenyan coast, the burden of moderate and severe CMDs among older adults is low; however, both OALWH and their HIV‐negative peers have a similar relatively high burden of mild depressive and anxiety symptoms. Our results also suggest that determinants of CMDs among OALWH in this setting are predominantly psychosocial factors. These results highlight the need for psychosocial interventions (at the family, community and clinical levels) to mitigate the risks of mild CMDs as they are known to be potentially debilitating.